2021
DOI: 10.1590/1413-81232020261.06892019
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fruits, vegetables, and ultra-processed foods consumption among infants

Abstract: The objective was to evaluate the influence of individual and contextual determinants on infant’s consumption of fruits and vegetables (FV), and ultra-processed foods (UPF). The data was obtained from the Survey of Prevalence of Breastfeeding in Brazilian Municipalities, 2008. A representative sample of 14,326 infants 6-11.9 months old, from seventy-five municipalities of São Paulo state was evaluated. The influence of determinants on FV and UPF consumption was analyzed using Poisson multilevel regression. Mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
1
3
0
4
Order By: Relevance
“…In the present study, among the possible factors associated with high consumption of ultra‐processed foods, logistic regressions showed that, at 9 months, breastfed children had a lower likelihood of high consumption of ultra‐processed food. This finding is in line with studies reporting that breast milk consumption is associated with lower consumption of ultra‐processed foods among children between 6 and 12 months (Fonseca et al, 2019 ; Giesta et al, 2019 ; Passanha et al, 2021 ; Spaniol et al, 2020 ). A possible cause for this lower consumption of ultra‐processed food is that breastfeeding mothers tend to limit their children's exposure to and consumption of unhealthy foods (Dwyer, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, among the possible factors associated with high consumption of ultra‐processed foods, logistic regressions showed that, at 9 months, breastfed children had a lower likelihood of high consumption of ultra‐processed food. This finding is in line with studies reporting that breast milk consumption is associated with lower consumption of ultra‐processed foods among children between 6 and 12 months (Fonseca et al, 2019 ; Giesta et al, 2019 ; Passanha et al, 2021 ; Spaniol et al, 2020 ). A possible cause for this lower consumption of ultra‐processed food is that breastfeeding mothers tend to limit their children's exposure to and consumption of unhealthy foods (Dwyer, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…S. Costa et al, 2019;Filgueiras et al, 2019;Rauber et al, 2015;Spaniol et al, 2020). Some Brazilian researchers have performed an analysis of complementary feeding, considering the extent of food processing (Fonseca et al, 2019;Giesta et al, 2019;Passanha et al, 2021;Ribas et al, 2021;Santos et al, 2018). They concluded that the feeding practices of children between 4 and 24 months were inappropriate, with high ultra-processed food consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, maternal education was positively and strongly associated with children consumption of plant-based vitamin A-rich diet. Higher educational attainment is known to be an important factor for attitudes towards the consumption of the vitamin A-rich plant sources food groups [25,26,62,63]. Educated mothers are more likely to have nutrition literacy and healthier dietary practices, allowing them to mediate healthier diets for their children [64].…”
Section: Discussionmentioning
confidence: 99%
“…11 A baixa variedade de alimentos na dieta está associada à restrição do crescimento, agravamento das principais deficiências de micronutrientes, atraso intelectual, ganho de peso e, em longo prazo, ao desenvolvimento de doenças crônicas não transmissíveis. 12,13 Dados disponíveis no Brasil demonstram práticas inadequadas na AC tradicional como a oferta de alimentos não recomendados no primeiro ano de vida. 12,14,15 Mesmo com a crescente popularidade dos métodos de AC e os resultados promissores na diversidade alimentar 7 e exposição a vegetais 6 na alimentação infantil, há uma lacuna na literatura sobre se tais métodos impactam positivamente a variedade alimentar e consequentemente a presença de DAM.…”
Section: Introductionunclassified